APPLICATION OF GOOGLE CLASSROOM ON MATERIALS REPRESENT ABILITY AND WILL TO IMPROVE ENGLISH WRITING SKILLS - Anistyowati Anistyowati (STKIP PGRI Jombang, 2022)
As an effort to prevent the spread of the virus during the Covid-19 pandemic, the government issued a policy that schools ask their students to study at home. Starting March 16, 2020, the school implemented the online student learning method. The implementation of online learning is one of the learning models carried out during the pandemic, because the principle of educational policy during the Covid-19 pandemic is to prioritize the health and safety of students, educators, education staff, families, and society in general, in order to fulfill educational services during the pandemic. With the advancement of internet technology as it is today, there are many alternative means and media that can be used to carry out online learning, so that we can choose which one is most appropriate and can be applied to our students. Google Classroom is one of the applications that can be chosen because it provides convenience in learning as well as providing freedom (free) for its users. Besides, Google Classroom is relatively easy and known by students. This is because[v2] most internet users in our country use Google accounts to access their browsers or access websites.